2013
DOI: 10.1037/a0030287
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of daily cigarette smoking amount in dependent adults.

Abstract: Self-reported cigarettes per day (CPD) is a very common screening, as well as dependent or independent, measure in clinical and non-clinical research on smoking, but consistency of CPD across days in dependent smokers is uncertain. Adult dependent smokers (N=357; 170 men, 187 women) retrospectively reported “usual” CPD at screening and then prospectively self-monitored CPD on 3 consecutive days of one week during an ad libitum baseline period. Participants were those recruited for later tests of brief medicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 34 publications
2
32
4
Order By: Relevance
“…Using Bedfont monitors, Erb, Raiff, Meredith, and Dallery (2014) identified CO values <8 ppm as maximizing both sensitivity and specificity for classifying smokers from nonsmokers. By contrast, Perkins et al (2013) found < 5 ppm to be the optimal cutoff for 24 hour abstinence when using the Vitalograph BreathCO monitor, similar to <4 ppm found by Javors, Hatch, and Lamb (2005), Cropsey et al (2014) and Emery and Levine (2015) when also using the Vitalograph monitor. This discrepancy suggests there may be variation between these brands of CO monitors in validating abstinence and raises concern over whether they can be used interchangeably.…”
Section: Introductionsupporting
confidence: 58%
See 3 more Smart Citations
“…Using Bedfont monitors, Erb, Raiff, Meredith, and Dallery (2014) identified CO values <8 ppm as maximizing both sensitivity and specificity for classifying smokers from nonsmokers. By contrast, Perkins et al (2013) found < 5 ppm to be the optimal cutoff for 24 hour abstinence when using the Vitalograph BreathCO monitor, similar to <4 ppm found by Javors, Hatch, and Lamb (2005), Cropsey et al (2014) and Emery and Levine (2015) when also using the Vitalograph monitor. This discrepancy suggests there may be variation between these brands of CO monitors in validating abstinence and raises concern over whether they can be used interchangeably.…”
Section: Introductionsupporting
confidence: 58%
“…Javors et al 2005; Perkins et al 2013), the Vitalograph monitors agreed with the Bedfont classifications 87.8% of the time. However, when the same criterion was met using the Vitalograph monitors, the Bedfont monitors agreed less than half of the time (48.5%), indicating reported results for abstinence rates in clinical trials could be influenced by the monitor used.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Former two methods show four to six time higher incidence of digit bias than latter one . Also prospective CPD data collection (Perkins et al, 2012) has twice less digit bias than retrospective CPD data collection technique. These methods are time consuming and resource intensive.…”
Section: Introductionmentioning
confidence: 99%